2023
DOI: 10.3389/fpsyt.2023.1130610
|View full text |Cite
|
Sign up to set email alerts
|

Universal prevention for non-suicidal self-injury in adolescents is scarce - A systematic review

Arne Bürger,
Cornelia von Schoenfeld,
Christin Scheiner
et al.

Abstract: Non-suicidal self-injury (NSSI) during adolescence is a high-risk marker for the development and persistence of mental health problems and has been recognized as a significant public health problem. Whereas targeted prevention has indeed shown to be effective in reducing NSSI and improve mental health problems, access to such programs is limited. By face validity, universal prevention of NSSI seems an ideal starting point for a stepped-care model to circumvent a lack of resources in the medical care system. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…This finding is consistent with previous research indicating that emotional abuse may directly affect an individual’s emotional regulation abilities, while sexual abuse and physical neglect may indirectly influence NSSI through the development of depression and anxiety (Brown et al, 2018 ). A recent review assessed universal strategies for preventing NSSI and found that none of the evaluated programs were effective in reducing the incidence or frequency of NSSI (Bürger et al, 2023 ). Our findings highlight the necessity of implementing targeted prevention interventions customized to individuals with varying depressive states.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with previous research indicating that emotional abuse may directly affect an individual’s emotional regulation abilities, while sexual abuse and physical neglect may indirectly influence NSSI through the development of depression and anxiety (Brown et al, 2018 ). A recent review assessed universal strategies for preventing NSSI and found that none of the evaluated programs were effective in reducing the incidence or frequency of NSSI (Bürger et al, 2023 ). Our findings highlight the necessity of implementing targeted prevention interventions customized to individuals with varying depressive states.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, according to the WHO, violence-related injuries are the main causes of death of children, with ~0.95 million children and young people under the age of 18 dying from injury and violence worldwide each year 8 . Furthermore, a cross-sectional assessment of adolescents involving 11 European countries suggested that 7.8% of adolescents suffered from repetitive nonsuicidal self-injury 9 , and it showed increasing prevalence at age 13–14, peaking at around age 15–16 10 . According to GBD 2017, the Eastern Mediterranean Region countries bear a heavy injury burden that largely impacts child and adolescent safety and health, and the leading cause of injury deaths and disability-adjusted life years (DALYs) was self-harm and interpersonal violence 11 .…”
Section: Introductionmentioning
confidence: 99%